Effectiveness of limited visual risk assessments in predicting urban tree storm failure in Wisconsin, U.S. - Larsen W. McBride; Ryan W. Klein; Andrew K. Koeser; Mysha K. Clarke; Richard J. Hauer; Thomas Ward; Timothy Bull; Chris Harchick (Urban Forestry & Urban Greening, 2026)

BoSapient®, a Cell-Based BoNT-A Potency Assay Optimized for Manual and Semi-Automated Procedures - F. Mark Dunning; Sara Hendrickson; Serena Wolfe; Dan Harding; Theresa Geurs; Timothy M. Piazza; Thomas A. Little; Ward C. Tucker (Toxicon, 2026)

Skill Testing Oxygen Data for Distribution Modeling of Marine Species - Julia Indivero; Sean C. Anderson; Lewis A. K. Barnett; John E. Pohl; Sean K. Rohan; Samantha Siedlecki; Eric J. Ward; Timothy E. Essington (Fisheries Oceanography, 2026)
Spatial models that identify statistical relationships between environmental conditions and species distributional data are commonly used in fisheries research to evaluate habitat suitability and predict distributional shifts, such as those driven by changing ocean temperature and oxygen levels. However, a lack of environmental data—particularly dissolved oxygen—at the same temporal and spatial resolution as biological data can limit these analyses. We evaluate the ability to predict bottom dissolved oxygen via imputation and extrapolation and with biophysical oceanographic models in the northeastern Pacific Ocean (Aleutian Islands, Eastern Bering Sea, Gulf of Alaska, British Columbia, and California Current). Specifically, we measure predictive skill compared to in situ observations (measured concurrently with bottom trawl data) for (1) predictions from an empirical statistical model fit to integrated dissolved oxygen observations and (2) a commonly used dynamical oceanographic model estimate of oxygen, the Global Oceanographic Biogeochemistry Hindcast (GOBH). Lastly, we evaluate how estimation and interpretation of a species distribution model are impacted by the use of different oxygen data sources. For year‐out cross‐validation, we find that the empirical statistical model predicts bottom dissolved oxygen for fish catch sampling events with relatively high accuracy in only certain regions (California Current and British Columbia) (root mean squared error [RMSE] ~ 16–30 μmol kg −1 ). Prediction skill was more than two times lower in Alaska regions that did not have extensive data (around −1 ). When applied to species distribution models, the estimated dissolved oxygen thresholds differed by 20–50 μmol kg −1 when fit to different dissolved oxygen data sources. We focus on oxygen in the northeastern Pacific, yet our approach is generalizable to other variables and systems. We recommend increased attention to validating oceanographic models when operationalized to fisheries applications and evaluating the robustness of conclusions to environmental covariate data sources.

Plasma membrane impacts of particulate matter on the blood-brain barrier - Chang Guo; Sanghamitra Mukhopadhyay; Laura Zanetti Domingues; Robert Lees; Esther Garcia Gonzalez; Benji Bateman; Andy Ward; Ludmila Mee; Rachel Smith; Timothy W. Gant; Ian Mudway (Science of The Total Environment, 2026)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Biogeochemical controls on iron speciation and cycling across upland to shoreline gradients in freshwater and estuarine coastal soils (Lake Erie and Chesapeake Bay, United States) - Lucie Stetten; Maxim I. Boyanov; Edward J. O'Loughlin; Shan Pushpajom Thomas; Kathleen R. Beilsmith; Roberta B. Peixoto; Fausto Machado-Silva; Donnie J. Day; Stephanie J. Wilson; Timothy W. Vugteveen; Allison N. Myers-Pigg; Opal Otenburg; et al. (Science of The Total Environment, 2025)

Manure temperature prediction for slurry storage in Sweden: Model validation including effects of shading, snow cover and mixing - Chih-Yu Hung; Kristina Mjöfors; Timothy Rennie; Brian Grant; Ward Smith; Andrew VanderZaag (Biosystems Engineering, 2024)

Drinking water sources, quality, and associated health outcomes in Appalachian Virginia: A risk characterization study in two counties - Alasdair Cohen; Md Rasheduzzaman; Bethesda O'Connell; Teresa Brown; Mami Taniuchi; Leigh-Anne Krometis; Alan Hubbard; Phillip Scheuerman; Marc Edwards; Amanda Darling; Blaine Pennala; Sarah Price; et al. (International Journal of Hygiene and Environmental Health, 2024)

Challenges in assessing and managing multi-hazard risks: A European stakeholders perspective - Robert Šakić Trogrlić; Karina Reiter; Roxana L. Ciurean; Stefania Gottardo; Silvia Torresan; Anne Sophie Daloz; Lin Ma; Noemi Padrón Fumero; Sharon Tatman; Stefan Hochrainer-Stigler; Marleen C. de Ruiter; Julius Schlumberger; et al. (Environmental Science & Policy, 2024)

Nitrate exposure from drinking water and dietary sources among Iowa farmers using private wells - Timothy G. Skalaban; Darrin A. Thompson; Jessica M. Madrigal; Benjamin C. Blount; Maria Morel Espinosa; Dana W. Kolpin; Nicole C. Deziel; Rena R. Jones; Laura Beane Freeman; Jonathan N. Hofmann; Mary H. Ward (Science of The Total Environment, 2024)

Development of Cell-Based Relative Potency Assays for Antibody-Based Therapeutic Drug Products Against Botulism - Timothy M. Piazza; Theresa L. Geurs; Serena K. Wolfe; Daniel Harding; Thomas A. Little; Ward C. Tucker (Toxicon, 2024)

Sensitive and Accurate Detection of Botulinum Neurotoxin Types A, B, E, and F From Diverse Food Samples Using the BoLISA® Assay - F. Mark Dunning; Timothy M. Piazza; Ward C. Tucker (Toxicon, 2024)

Extractability indices for screening coal combustion byproduct feedstocks for recovery of rare earth elements - Ward Burgess; Cheuk Fai Chiu; Timothy Cain; Elliot Roth; Murphy Keller; Evan Granite (International Journal of Coal Geology, 2024)

Emergent role of critical interfaces in the dynamics of intensively managed landscapes - Praveen Kumar; Alison Anders; Erin Bauer; Neal E. Blair; Molly Cain; Ashlee Dere; Jennifer Druhan; Timothy Filley; Christos Giannopoulos; Allison E. Goodwell; David Grimley; Diana Karwan; et al. (Earth-Science Reviews, 2023)

Great expectations: patients’ preferences for clinically significant results from genomic sequencing - Salma Shickh; Agnes Sebastian; Marc Clausen; Chloe Mighton; Christine Elser; Andrea Eisen; Larissa Waldman; Seema Panchal; Thomas Ward; June C. Carroll; Emily Glogowski; Kasmintan A. Schrader; et al. (Human Genetics, 2023)

Integrating management of marine activities in Australia - Robert L. Stephenson; Alistair J. Hobday; Ian Butler; Toni Cannard; Mel Cowlishaw; Ian Cresswell; Christopher Cvitanovic; Jon C. Day; Kirstin Dobbs; Leo X.C. Dutra; Stewart Frusher; Maree Fudge; et al. (Ocean & Coastal Management, 2023)

Adsorption and degradation of neonicotinoid insecticides in agricultural soils - Yang Li; Yadong Li; Guihong Bi; Timothy J. Ward; Lin Li (Environmental Science and Pollution Research, 2023)

Individual and collective behaviour of fish subject to differing risk-level treatments with a sympatric predator - Alexander D. M. Wilson; Timothy M. Schaerf; Ashley J. W. Ward (Behavioral Ecology and Sociobiology, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

A hidden Markov model for estimating age‐specific survival when age and size are uncertain - Timothy A. Gowan; Michael D. Tringali; Jeffrey A. Hostetler; Julien Martin; Leslie I. Ward‐Geiger; Jennifer M. Johnson (Ecology, 2021)
Estimates of age‐specific survival probabilities are needed for age‐structured population models and to inform conservation decisions. However, determining the age of individuals in wildlife populations is often problematic. We present a hidden Markov model for estimating age‐specific survival from capture–recapture or capture–recapture–recovery data when age is unknown and indicators of age, such as size and growth layer counts, are imprecise. The model is evaluated through simulations, and its implementation is illustrated with maximum likelihood and Bayesian approaches in commonly used software. The model is then applied to genetic capture–recapture data of Florida manatees to estimate age‐ and time‐variant survival probabilities. The approach is broadly applicable to studies aiming to quantify age‐specific effects of environmental change and management actions on population dynamics, including studies that rely on minimally invasive methods such as genetic and photo identification.

Risks on global financial stability induced by climate change: the case of flood risks - Antoine Mandel; Timothy Tiggeloven; Daniel Lincke; Elco Koks; Philip Ward; Jochen Hinkel (Climatic Change, 2021)

Socio‐ecological drivers of vertebrate biodiversity and human‐animal interfaces across an urban landscape - James M. Hassell; Judy M. Bettridge; Melissa J. Ward; Allan Ogendo; Titus Imboma; Dishon Muloi; Francesco Fava; Timothy P. Robinson; Michael Begon; Eric M. Fèvre (Global Change Biology, 2021)
Urbanization can have profound impacts on the distributional ecology of wildlife and livestock, with implications for biodiversity conservation, ecosystem services and human health. A wealth of studies have assessed biotic responses to urbanization in North America and Europe, but there is little empirical evidence that directly links human activities to urban biodiversity in the tropics. Results from a large‐scale field study conducted in Nairobi, Kenya, are used to explore the impact of human activities on the biodiversity of wildlife and livestock with which humans co‐exist across the city. The structure of sympatric wildlife, livestock and human populations are characterized using unsupervised machine learning, and statistical modelling is used to relate compositional variation in these communities to socio‐ecological drivers occurring across the city. By characterizing landscape‐scale drivers acting on these interfaces, we demonstrate that socioeconomics, elevation and subsequent changes in habitat have measurable impacts upon the diversity, density and species assemblage of wildlife, livestock and humans. Restructuring of wildlife and livestock assemblages (both in terms of species diversity and composition) has important implications for the emergence of novel diseases at urban interfaces, and we therefore use our results to generate a set of testable hypotheses that explore the influence of urban change on microbial communities. These results provide novel insight into the impact of urbanization on biodiversity in the tropics. An understanding of associations between urban processes and the structure of human and animal populations is required to link urban development to conservation efforts and risks posed by disease emergence to human health, ultimately informing sustainable urban development policy.

Locomotion, interactions and information transfer vary according to context in a cryptic fish species - Stella A. Encel; Timothy M. Schaerf; Joseph T. Lizier; Ashley J. W. Ward (Behavioral Ecology and Sociobiology, 2021)

Coral Reef Monitoring, Reef Assessment Technologies, and Ecosystem-Based Management - David O. Obura; Greta Aeby; Natchanon Amornthammarong; Ward Appeltans; Nicholas Bax; Joe Bishop; Russell E. Brainard; Samuel Chan; Pamela Fletcher; Timothy A. C. Gordon; Lew Gramer; Mishal Gudka; et al. (Frontiers in Marine Science, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Photodegradation of clothianidin and thiamethoxam in agricultural soils - Yang Li; Yadong Li; Yiming Liu; Timothy J. Ward (Environmental Science and Pollution Research, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Body size drives allochthony in food webs of tropical rivers - Timothy D. Jardine; Thomas S. Rayner; Neil E. Pettit; Dominic Valdez; Douglas P. Ward; Garry Lindner; Michael M. Douglas; Stuart E. Bunn (Oecologia, 2017)

Survival, Reproduction and Growth of the Marine Amphipod, Leptocheirus plumulosus, Following Laboratory Exposure to Copper-Spiked Sediment - Timothy J. Ward; Karin E. Gaertner; Joseph W. Gorsuch; Daniel J. Call (Bulletin of Environmental Contamination and Toxicology, 2015)

Survival and Growth of the Marine Polychaete, Neanthes arenaceodentata, Following Laboratory Exposure to Copper-Spiked Sediment - Timothy J. Ward; Karin E. Gaertner; Joseph W. Gorsuch; Daniel J. Call (Bulletin of Environmental Contamination and Toxicology, 2015)

The influence of nutritional state on individual and group movement behaviour in shoals of crimson-spotted rainbowfish (Melanotaenia duboulayi) - Matthew J. Hansen; Timothy M. Schaerf; Ashley J. W. Ward (Behavioral Ecology and Sociobiology, 2015)

Does flood rhythm drive ecosystem responses in tropical riverscapes? - Timothy D. Jardine; Nicholas R. Bond; Michele A. Burford; Mark J. Kennard; Douglas P. Ward; Peter Bayliss; Peter M. Davies; Michael M. Douglas; Stephen K. Hamilton; John M. Melack; Robert J. Naiman; Neil E. Pettit; et al. (Ecology, 2015)
Biotic communities are shaped by adaptations from generations of exposure to selective pressures by recurrent and often infrequent events. In large rivers, floods can act as significant agents of change, causing considerable physical and biotic disturbance while often enhancing productivity and diversity. We show that the relative balance between these seemingly divergent outcomes can be explained by the rhythmicity, or predictability of the timing and magnitude, of flood events. By analyzing biological data for large rivers that span a gradient of rhythmicity in the Neotropics and tropical Australia, we find that systems with rhythmic annual floods have higher fish species richness, more stable avian populations, and elevated rates of riparian forest production compared with those with arrhythmic flood pulses. Intensification of the hydrological cycle driven by climate change, coupled with reductions in runoff due to water extractions for human use and altered discharge from impoundments, is expected to alter the hydrologic rhythmicity of floodplain rivers with significant consequences for both biodiversity and productivity.

Global conservation status and research needs for tarpons (Megalopidae), ladyfishes (Elopidae) and bonefishes (Albulidae) - Aaron J Adams; Andrij Z Horodysky; Richard S McBride; Kathryn Guindon; Jonathan Shenker; Timothy C MacDonald; Heather D Harwell; Rocky Ward; Kent Carpenter (Fish and Fisheries, 2014)
We assessed the taxonomic diversity, geographic distributions, life history, ecology and fisheries of tarpons, ladyfishes and bonefishes (members of the subdivision Elopomorpha), which share many life history and habitat use characteristics that make them vulnerable to environmental and anthropogenic stresses in coastal environments. This assessment of Red List status for the International Union for the Conservation of Nature reveals three species considered near threatened or vulnerable, three species of least concern, and 11 data‐deficient species. Although the taxonomy of tarpons appears stable, it is less so for ladyfishes and bonefishes. In aggregate, these species are distributed circumtropically and foray into temperate zones. Although they spawn in marine habitats, larvae of many species disperse into estuarine habitats, which are declining in area or degrading in quality. Several species support high‐value recreational fisheries, or culturally important small‐scale commercial and artisanal fisheries. Nonetheless, no formal stock assessment exists for any species, so improved data collection, information sharing and assessment techniques should facilitate socio‐economic development of individual fisheries. Catch‐and‐release recreational fisheries that promote conservation of tarpon and bonefishes in some regions are promising models to improve the conservation status of these fishes elsewhere, as well as the economic development of these fishing communities. Most tarpons, ladyfishes and bonefishes likely face significant challenges from anthropogenically mediated habitat loss and alteration, and several are vulnerable to both habitat degradation and overfishing. Broader protection and enhancements to fisheries habitat in all regions will benefit these as well as many other coastal fishery species.

Methane indicator values for peatlands: a comparison of species and functional groups - Alan Gray; Peter E. Levy; Mark D. A. Cooper; Timothy Jones; Jenny Gaiawyn; Sarah R. Leeson; Susan E. Ward; Kerry J. Dinsmore; Julia Drewer; Lucy J. Sheppard; Nick J. Ostle; Chris D. Evans; et al. (Global Change Biology, 2013)
Previous studies have shown a correspondence between the abundance of particular plant species and methane flux. Here, we apply multivariate analyses, and weighted averaging, to assess the suitability of vegetation composition as a predictor of methane flux. We developed a functional classification of the vegetation, in terms of a number of plant traits expected to influence methane production and transport, and compared this with a purely taxonomic classification at species level and higher. We applied weighted averaging and indirect and direct ordination approaches to six sites in the United Kingdom, and found good relationships between methane flux and vegetation composition (classified both taxonomically and functionally). Plant species and functional groups also showed meaningful responses to management and experimental treatments. In addition to the United Kingdom, we applied the functional group classification across different geographical regions (Canada and the Netherlands) to assess the generality of the method. Again, the relationship appeared good at the site level, suggesting some general applicability of the functional classification. The method seems to have the potential for incorporation into large‐scale (national) greenhouse gas accounting programmes (in relation to peatland condition/management) using vegetation mapping schemes. The results presented here strongly suggest that robust predictive models can be derived using plant species data (for use in national‐scale studies). For trans‐national‐scale studies, where the taxonomic assemblage of vegetation differs widely between study sites, a functional classification of plant species data provides an appropriate basis for predictive models of methane flux.

Methane emissions from soils: synthesis and analysis of a large UK data set - Peter E. Levy; Annette Burden; Mark D. A. Cooper; Kerry J. Dinsmore; Julia Drewer; Chris Evans; David Fowler; Jenny Gaiawyn; Alan Gray; Stephanie K. Jones; Timothy Jones; Niall P. McNamara; et al. (Global Change Biology, 2012)
Nearly 5000 chamber measurements of CH 4 flux were collated from 21 sites across the U nited K ingdom, covering a range of soil and vegetation types, to derive a parsimonious model that explains as much of the variability as possible, with the least input requirements. Mean fluxes ranged from −0.3 to 27.4 nmol CH 4 m −2 s −1 , with small emissions or low rates of net uptake in mineral soils (site means of −0.3 to 0.7 nmol m −2 s −1 ) and much larger emissions from organic soils (site means of −0.3 to 27.4 nmol m −2 s −1 ). Less than half of the observed variability in instantaneous fluxes could be explained by independent variables measured. The reasons for this include measurement error, stochastic processes and, probably most importantly, poor correspondence between the independent variables measured and the actual variables influencing the processes underlying methane production, transport and oxidation. When temporal variation was accounted for, and the fluxes averaged at larger spatial scales, simple models explained up to ca. 75% of the variance in CH 4 fluxes. Soil carbon, peat depth, soil moisture and pH together provided the best sub‐set of explanatory variables. However, where plant species composition data were available, this provided the highest explanatory power. Linear and nonlinear models generally fitted the data equally well, with the exception that soil moisture required a power transformation. To estimate the impact of changes in peatland water table on CH 4 emissions in the U nited K ingdom, an emission factor of +0.4 g CH 4 m −2 yr −1 per cm increase in water table height was derived from the data.

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Age-dependent effects of the cannabinoid CB1 antagonist SR141716A on food intake, body weight change, and pruritus in rats - Sara Jane Ward; Timothy W. Lefever; Scott M. Rawls; Garth T. Whiteside; Ellen A. Walker (Psychopharmacology, 2009)

Comparative genomics reveals functional transcriptional control sequences in the Prop1 gene - Robert D. Ward; Shannon W. Davis; MinChul Cho; Constance Esposito; Robert H. Lyons; Jan-Fang Cheng; Edward M. Rubin; Simon J. Rhodes; Lori T. Raetzman; Timothy P. L. Smith; Sally A. Camper (Mammalian Genome, 2007)

Human acetylator genotype: Relationship to colorectal cancer incidence and arylamine N-acetyltransferase expression in colon cytosol - Jose W. Rodriguez; Ward G. Kirlin; Ronald J. Ferguson; Mark A. Doll; Kevin Gray; Timothy D. Rustan; Mark E. Lee; Katherine Kemp; Paul Urso; David W. Hein (Archives of Toxicology, 1993)